Eating behavior by sleep duration in the Hispanic Community Health Study/Study of Latinos. (1st December 2015) - Mossavar-Rahmani, Yasmin; Jung, Molly; Patel, Sanjay R.; Sotres-Alvarez, Daniela; Arens, Raanan; Ramos, Alberto; Redline, Susan; Rock, Cheryl L.; Van Horn, Linda
Abstract: Sleep is an important pillar of health and a modifiable risk factor for diabetes, stroke and obesity. Little is known of diet and sleep patterns of Hispanics/Latinos in the US. Here we examine eating behavior as a function of sleep duration in a sub-sample of 11, 888 participants from the Hispanic Community Health Study/Study of Latinos, a community-based cohort study of Hispanics aged 18–74 years in four US cities. Using a cross-sectional probability sample with self-report data on habitual sleep duration and up to two 24-h dietary recalls, we quantified the Alternative Healthy Eating Index (AHEI-2010) score, a measure of diet quality, and intake of selected nutrients related to cardiovascular health. Linear regression models were fit to estimate least-square means of usual nutrient intake of saturated fats, potassium density, fiber, calcium, caffeine and the AHEI-2010 score by sleep duration adjusting for age, sex, Hispanic/Latino background, income, employment status, education, depressive symptomology, and years lived in the US. Distribution of calories over the day and association with sleep duration and BMI were also examined. Short sleepers (≤6 h) had significantly lower intake of potassium, fiber and calcium and long sleepers (≥9 h) had significantly lower intake of caffeine compared to others sleepers after adjusting for covariates. However no difference in the AHEI-2010 score was seen by sleep duration. Significantly more long sleepers, compared to intermediate and short sleepers, reported having ≥30% total daily calories before bedtime. Not consuming a snack or meal within 3 h before bedtime was associated with higher AHEI-2010 scores. These findings identify novel differences in dietary patterns by sleep duration in a Hispanic/Latino cohort in the U.S. ClinicalTrials.gov Identifier: NCT02060344 Highlights: This study identified novel differences in dietary patterns by sleep duration in a Hispanic/Latino population in the US. Not consuming a snack or meal within 3 h before bedtime was associated with higher AHEI-2010 scores and lower energy intake. Short sleepers (≤6 h) had significantly lower intakes of potassium, fiber and calcium. Long sleepers (≥9 h) had significantly lower intake of caffeine compared to others sleepers. No difference in the AHEI-2010 score was seen by sleep duration.